Implementation of Speaking Assessment in Primary Grade 3 - Purwaning, Alynia; Muamaroh, Muamaroh; Hikmat, Mauly Halwat; Wijayanto, Agus; Sutopo, Anam (Samudra Publisher, 2026)
Abstract This paper explores the strategic implementation of speaking assessments for the students of grade 3 in primary school. However, the primary challenges in speaking assessment include psychological barriers such as performance anxiety and a lack of authentic assessment instruments. This study aims to formulate an implementation strategy for speaking assessments that are effective, supportive, and appropriate for students in the concrete operational stage of development. This study employs a qualitative approach using literature review and classroom observation methods. Data were collected through curriculum analysis, a review of child developmental psychology literature, and an evaluation of various formative assessment techniques. Data analysis was conducted descriptively to determine the suitability of assessment techniques with the characteristics of eight to nine-year-old students. The findings indicate that the implementation of speaking assessment in Grade 3 is most effective when utilizing performance-based assessment integrated into daily activities, such as